Features of the dynamics of the cellular composition of the thymic subcapsular zone in the postnatal period after intrauterine exposure to staphylococcal anatoxi - Aravitskiy, E. O.; Аравіцький, Євген Олегович (Berlin : MDPC Publishing, 2024)
Aim: to identify the features of the dynamics of the relative quantity of cortical substance lymphocytes in the thymus of rats during the first month of life after prenatal exposure to staphylococcal anatoxin.
Keywords: тези доповідей